KOMODIFIKASI BARONGSAI MENJAGA TRADISI MENEGOSIASI PASAR - Moch. Choirul Arif; GR. Lono Lastoro Simatupang; Budiawan Budiawan (Jurnal Kawistara, 2016)
After the fall of the Soeharto regime was like the fresh air for the ethnic Chinese in Indonesia inarticulating cultural identities, especially after the issuance of Presidential decree Number 6 of 2000which revoked Presidential Instruction Number 14 of 1967 on religion, beliefs, and customs of China.With that Presidential decree, Chinese people were free to celebrate the religious ceremony and customs,as well as featuring Barongsai (Lion Dance) in front of public. Consequently, Barongsai became popularand transformed into a cultural icon as well as “obligatory menu” for city event. Barongsai allegedlyunderwent commodification along with its popularity. However, that signal was responded byBarongsai activists as the consequence of efforts to survive and conquer the market. Through the mindsetof yin and yang, commodification discourse is abrogated and appropriated by Barongsai activists, socommodification is not just an effort to maintain and preserve the ancestral cultural heritage, identity,and cultural pride due to the accomplishments achieved